The Influence of Toko Kopi Tuku's Marketing Communication on the Purchase Intentions of Generations Y and Z - Timothy Nathaniel; Sarah Samaria (Jurnal Komunikasi dan Bisnis, 2025)
Coffee is now inseparable from the lives of Indonesian people, making national coffee production increase to 756.1 thousand tons by 2023. More and more coffee shops with new concepts make competition tighter, so marketing communication is needed to win the competition. One of the well-known coffee shops in Indonesia is Toko Kopi Tuku. Effective marketing is the key to attracting consumer attention and increasing purchase interest. However, there are challenges in understanding the differences in consumer characteristics between generations Y and Z. Generation Y values a balance of product quality and value, and tends to be loyal to brands that offer added value and consistent quality. Generation Z seeks unique, personalized, authentic experiences, and is more critical and independent in making purchasing decisions. These differences demand the right marketing communication strategy to attract both segments. This study aims to find out the effect of Toko Kopi Tuku's marketing communication on generation Y and Z's purchase intention. The study used a quantitative approach with a population of 169,789 Instagram followers @tokokopituku and a sample of 100 people. Purposive sampling is used with the criteria that respondents are Generation Y or Z, know, and have bought Tuku Coffee Shop. The results showed that Marketing Communication had a positive effect in a moderate level on the Purchase Intention variable (Y), which was 56.8%. The remaining 43.2% is influenced by other variables outside this study.